Technology and Freudian Discontent: Freud’s‘Muffled’ Meliorism and the Problem of Human Annihilation - Holowchak, M. Andrew (Sophia, 2010)
This paper is a comprehensive investigation of Freud’s views on technology and human well-being, with a focus on ‘Civilization and Its Discontents’. In spite of his thesis in ‘Civilization and Its Discontents’, I shall argue that Freud, always in some measure under the influence of Comtean progressivism, was consistently a meliorist: He was always at least guardedly optimistic about the realizable prospect of utopia, under the ‘soft dictatorship’ of reason and guided by advances in science and technology, in spite of due recognition in his later years of the possibility of annihilation through technological advances in warfare. The possibility of human annihilation, then, muffled Freud’s meliorism. Freud’s ‘muffled meliorism’, however, was not a quiet commitment to viewing technology as something good. Ultimately, Freud steered a middle course between techno-advocacy and techno-antagonism. The technologies of science, like the discoveries of psychoanalysis, were tools for humans that could be used for human betterment or, as war showed, for human degeneration.